Glycan microarray analysis of Candida -related antibodies in human and mice sera guides biomarker discovery and vaccine development - Emelie E. Reuber; Emer Hickey; Arnab Pradhan; Rosanne Sprute; Tilman Lingscheid; Pinkus Tober-Lau; Ian Leaves; Mark H. T. Stappers; Florian Kurth; Mariolina Bruno; Mihai G. Netea; Leif E. Sander; et al. (Proceedings of the National Academy of Sciences, 2025)
Invasive, high-mortality yeast infections caused by pathogenic Candida species are the most common fungal nosocomial bloodstream infections. The World Health Organization (WHO) has called for improved prevention and diagnostic strategies for fungal pathogens. Here, we demonstrate that Candida -related antibodies can be detected using glycan microarrays containing synthetic glycans to guide the discovery of oligosaccharide epitopes for diagnostics and vaccine design. Pure, synthetic mannans and β -glucans, resembling carbohydrates found on the surface of Candida spp., were employed to screen and compare sera from infected humans and mice with noninfected individuals. IgM antibodies directed toward β -glucans were observed shortly after infection, and after a longer time of infection, IgM and IgG antibodies that preferentially recognize mannans. Phosphodiester-linked mannosides and the β -(1,2)-mannose monomer help to distinguish different Candida spp. The tetrasaccharide antigen β -(1,2)Man- α -(1,2)Man- α -(1,2)Man- α -(1,2)Man, and the pentasaccharide antigens α -(1,2)Man- α -(1,3)Man- α -(1,2)Man- α -(1,2)Man- α -(1,2)Man and β -(1,3)Glc- β -(1,3)Glc- β -(1,3)Glc-[ β -(1,6)Glc]- β -(1,3)Glc were identified as potential epitopes for detection, e.g., through monoclonal antibody lateral flow tests, and the development of glycoconjugate or monoclonal antibody vaccines against Candida.